Temporal patterns of abundance and waste use by Kelp Gulls at a urban and fishery waste tip in northern coastal Patagonia, Argentina - Giaccardi, Micel (2004)
We quantified the use by Kelp Gulls (Larus dominicanus) of urban and fishery waste sites at Puerto Madryn, Argentina, during 1996 and 1997. Kelp Gulls were present at all monthly counts made at both waste sites throughout the two years of the study. Total numbers of gulls in each month were high and variable, with a mean of 4724 and 4612 individuals in 1996 and 1997, respectively. The mean number of gulls at the fishery waste site was significantly larger than at the urban waste site (3767 vs 901). Adult Kelp Gulls were significantly more abundant than non-adult gulls at every count at both the urban and fishery waste sites (mean = 811 vs 91 and 3147 vs 628, respectively). Among the younger age classes, individuals in their third year were the least abundant. The proportion of adults with respect to total gulls present was high during all visits to both sites, although it showed a slight decrease in the fishery waste site during the breeding season. During the breeding season, the number of gulls varied significantly throughout the day at both sites while, during the non-breeding season, numbers varied significantly only in the urban waste site. The Puerto Madryn fishery waste site constitutes a more attractive food source than the urban waste site probably due to the higher quality and quantity of discarded food. The use of waste sites at Puerto Madryn may be enhancing gull breeding success and individual survival during the winter, particularly of young birds. Potential conflicts due to Kelp Gull use of waste sites and the effects on their populations could be minimized by adequate urban and fish waste management